PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY PADA MATA PELAJARAN INSTALASI MOTOR LISTRIK - Pradipta, Moh. Alfiansyah Putera; Fransisca, Yulia; Aribowo, Widi; B., I Gusti Putu Asto (Universitas Negeri Surabaya, 2021)
Installation of electric motors is the most important part in the industrial environment and the environment around the house. Installing an electric motor is very dangerous if there is a wrong connection of the cable and it can be fatal for human safety. During the Covid-19 pandemic, schools must go online to avoid the corona virus. While doing online, many SMK students do not understand the components of the electric motor installation, due to the absence of a practicum to facilitate learning. This study aims to determine student learning outcomes using Augmented Reality applications when online learning is carried out. This study uses a PreExperimental Design research method with a One-shot Case Study model. The subjects of this study were students of class XI SMK PGRI 1 SURABAYA Electrical Power Utilization Engineering class with 25 students. The results of the posttest test carried out by students the data obtained with an average value of 86.2 and a standard deviation of 5.05. The normality test of the data is not normally distributed. Results of data analysis with a significance level > 0.05 is 0.005, so the data is not normally distributed. For data that cannot be normally distributed using the nonparametric test and binomial test, the results of data analysis are 0.043 so that H0 is rejected and H1 is accepted. It was concluded that the average student learning outcomes on the component material of the electric motor installation were not equal to 75 or more than the KKM value of 75.